2013
DOI: 10.1007/s00436-013-3419-y
|View full text |Cite
|
Sign up to set email alerts
|

First identification of four trypanorhynchid cestodes: Callitetrarhynchus speciouses, Pseudogrillotia sp. (Lacistorhynchidae), Kotorella pronosoma and Nybelinia bisulcata (Tentaculariidae) from Sparidae and Mullidae fish

Abstract: Four previously unrecognized trypanorhynchids are described based on fish specimens from Sparidae and Mullidae host fish of the Red Sea. From September 2010 to June 2011, 66 specimens of the sea bream Pagrus pagrus (F: Sparidae) and 43 of the red mullet Mullus barbatus (F: Mullidae) were purchased from markets in the Suez and Hurghada cities of the Red Sea. The fishes were measured, and their organs investigated for helminth infections. Forty-one (37.6 %) out of the 109 fish specimens investigated were parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…7 (7′), while in C. speciosus they are almost equal in size. By morphometrical comparison ( Table 1 ), the parasite from the present study mostly resembles to C. gracilis in Lethrinus nebulosus and in Carangoides malabaricus y [18] , [19] , [36] , [37] , but showing minor variation in the dimensions of the different body parts.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…7 (7′), while in C. speciosus they are almost equal in size. By morphometrical comparison ( Table 1 ), the parasite from the present study mostly resembles to C. gracilis in Lethrinus nebulosus and in Carangoides malabaricus y [18] , [19] , [36] , [37] , but showing minor variation in the dimensions of the different body parts.…”
Section: Discussionmentioning
confidence: 88%
“…In Egypt, most of the previous studies were carried out on trypanorhynchids from marine fish in the Red Sea [3] , [17] , [18] , and there are no records for their existence in little tunny from the Egyptian Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…This study is the third report of Nybelinia species from fish from the Gulf of Suez, Red Sea, Egypt. The first report was by Morsy et al (2013) as it reported the presence of Nybelinia narinari and N. bisulcata from Pagrus pagrus. The second report for Palm & Walter (1999) recognized adults of N. africana from Carcharhinus melanopterus.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies were done on trypanorhynchids in marine fish from the Red Sea. Egyptian studies include Abdou (2000Abdou ( , 2001Abdou ( , 2005, Abdou & Palm (2008), and Morsy et al (2013). Papers from Saudi Arabia include those of Abu-Zinada (1998) and Toula (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the order Trypanorhyncha Diesing (1863) represent parasitic cestodes of fish and sea invertebrates; adults infect the stomach and intestines of sharks and rays as definitive hosts, while the larval stages are found in the musculature and coelomatic cavity of teleosteans as intermediate hosts (Campbell and Beveridge, 1994;Morsy et al, 2013;Santoro et al, 2020). Detection of these parasites among infected fish poses marketing problems (Morsy et al, 2013). Humans can be accidentally infected by larvae of Trypanorhyncha after ingesting raw fish meat which, in most cases, leads to allergic reactions.…”
Section: Introductionmentioning
confidence: 99%